New and poorly known ferns from the Santa Clara Formation, Late Triassic, Sonora, NW Mexico; III Marattiales. Tranquilia Herbst—a Panamerican dimorphic genus - Reinhard Weber (Revista Mexicana de Ciencias Geológicas)
The dimorphic marattialian fern Tranquilia whitneyi (Newberry) Herbst - formerly “Alethopteris whitneyi Newberry” and “Pecopteris falcatus Emmons”- from the Carnian (and perhaps Norian?) Santa Clara Formation of central Sonora, NW Mexico, is redescribed. Most of the older specimens of this species were either sterile or fertile… download the full paper in PDF.